Set up a proportion: x/y = x/y
(.75)/(15) = (x)/(25)
Then cross multiply:
(.75)(25) = (15)(x)
18.75 = 15x
x = 1.25 or (5/4)
There you go :)
3x - 6y = -2
-6y = -3x - 2, divide through by -1
6y = 3x + 2, divide through by 6
y = 3x/6 + 2/6
y = x/2 + 1/3
Answer:
The inverse f-1(x) = ( x - 2) / 2.
Step-by-step explanation:
Let 2x + 1 = y
Now find x in terms of y:
2x = y - 1
x = (y - 1) / 2
Replace the x by the inverse f-1(x) and the y by x, so we have:
f-1(x) = ( x - 2) / 2.
Answer:
19.1628873772
Step-by-step explanation:
50.70500 ÷ 2.64600 = 19.1628873772
Answer:
x = -2
Step-by-step explanation:
x+8 = 2x +10
-2x + x = 10-8
-x = 2
divide both side by -1
answer -- x = -2